2021
DOI: 10.1007/s00384-021-03887-w
|View full text |Cite
|
Sign up to set email alerts
|

The middle rectal artery detected by contrast-enhanced magnetic resonance imaging predicts lateral lymph node metastasis in lower rectal cancer

Abstract: Purpose Lateral lymph node (LLN) metastasis is one of the leading causes of local recurrence in patients with lower rectal cancer. Unfortunately, no diagnostic biomarkers are currently available that can predict LLN metastasis preoperatively. Accordingly, we investigated the relationship between the middle rectal artery (MRA) identified by contrast-enhanced magnetic resonance imaging (ceMRI) and LLN metastases. Methods Data from 102 patients with lower rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…There are studies in which the vessel was not found in any cases (Aigner et al, 2004; Schuurman et al, 2009), as well those that report its presence in all the cases studied (Adachi, 1928; Havenga et al, 1996; Ishii et al, 2018; Wei & Xiaoming, 2020). Similar prevalence of the MAA to the PPE of the current meta‐analysis was noted by DiDio et al (1986), Iwasa et al (2021), Jones et al (1999), Roberts and Krishingner (1967), Shafik and Mostafa (1996), and Widmer (1955). More detailed results on the prevalence of the MAA in the included studies can be found in Table 1.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…There are studies in which the vessel was not found in any cases (Aigner et al, 2004; Schuurman et al, 2009), as well those that report its presence in all the cases studied (Adachi, 1928; Havenga et al, 1996; Ishii et al, 2018; Wei & Xiaoming, 2020). Similar prevalence of the MAA to the PPE of the current meta‐analysis was noted by DiDio et al (1986), Iwasa et al (2021), Jones et al (1999), Roberts and Krishingner (1967), Shafik and Mostafa (1996), and Widmer (1955). More detailed results on the prevalence of the MAA in the included studies can be found in Table 1.…”
Section: Discussionsupporting
confidence: 88%
“…Having removed duplicates ( n = 66), 449 records were screened against the inclusion and exclusion criteria, based on their title and abstract. A full text analysis was undertaken on 105 potentially eligible studies, leading to identification of 28 works that were included in this systematic review and meta‐analysis (Adachi, 1928; Aigner et al, 2004; Ayoub, 1978; Bilhim et al, 2013; Boxall et al, 1963; DiDio et al, 1986; Drummond, 1914; Havenga et al, 1996; Ishii et al, 2018; Iwasa et al, 2021; Jiang et al, 2006; Jones et al, 1999; Lin et al, 2010; Lipshutz, 1918; Muntean, 1999; Naguib et al, 2008; Naidoo et al, 2018; Nano et al, 1998, 2000; Parsons & Keith, 1897; Roberts & Krishingner, 1967; Sato & Sato, 1991; Schuurman et al, 2009; Shafik & Mostafa, 1996; Vogel & Klosterhalfen, 1988; Wei & Xiaoming, 2020; Widmer, 1955; Zhang et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…3,8 However, a very recent study using contrast-enhanced MRI in 102 individuals reported the presence of the MRA in a similar percentage of cases (65.7%) as in our investigation (71.4%). 19…”
Section: Discussionmentioning
confidence: 99%
“…This correlation emphasizes not only the key role of the MRA for lateral tumor spread but also the clinical significance of the MRA in the selection of tailored treatment regimens. 19…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation